Case report: Use of three-dimensional technology in criss-cross heart with double outlet right ventricle - Alifu, Ailixiati; Wang, Haifan; Su, Yuntian; Chen, Renwei (Frontiers in Cardiovascular Medicine, 2023)
Background: In this case report, we utilized a three-dimensional printing model to replicate the complex anatomy of a criss-cross heart with double outlet right ventricle - an extremely rare congenital cardiac abnormality. This approach facilitated our understanding of the patient's unique condition and enabled us to plan the surgical procedure with greater precision. Case presentation: Our department received a 13-year-old female patient who presented with a pronounced heart murmur and a decrease in exercise capacity. Subsequent two-dimensional imaging revealed the presence of a criss-cross heart with double outlet right ventricle - an intricate and uncommon cardiac malformation that poses challenges for accurate visualization through conventional two-dimensional modalities. To address this challenge, we constructed and printed a three-dimensional model using computed tomography data, which enabled us to visualize and understand the complex intracardiac structures and plan surgical interventions with greater precision. Using this approach, we successfully performed a right ventricular double outlet repair, and the patient made a full recovery following the procedure. Conclusion: The criss-cross heart with double outlet right ventricle constitutes a complex and uncommon cardiac anomaly that poses considerable challenges in terms of diagnosis and surgical intervention. Employing three-dimensional modeling and printing represents a promising approach, given its potential to enhance the precision and comprehensiveness of the anatomical evaluation of the heart. As a result, this method holds significant promise in facilitating accurate diagnosis, meticulous surgical planning, and ultimately improving clinical outcomes for patients affected by this condition.